Penyusunan Laporan Pajak Untuk Yayasan Pantau Usaha Indonesia (BWI) - Nurmansyah, Agung; Kristianto, Giovanny Bangun; Istiningrum, Farida (Universitas Harapan Bangsa, 2025)
The issue of illegal parking in Banyumas Regency has caused negative impacts such as traffic congestion, road user inconvenience, and disruption of traffic order. To support enforcement efforts, a technology-based solution capable of real-time monitoring is required. This community service activity aims to introduce and discuss an illegal parking monitoring system based on Computer Vision in collaboration with the Department of Transportation and regional parking coordinators in Banyumas. The implementation method includes system concept presentations, technology demonstrations, and discussion forums to gather input related to technical needs and field policy considerations. The results of the activity indicate interest from the Department of Transportation and parking coordinators in utilizing this technology, particularly in supporting the effectiveness of supervision and the enforcement of parking regulations. This activity is expected to serve as an initial step toward collaboration between academia and local government in applying smart technology to improve order, safety, and convenience in Banyumas Regency.